2012
DOI: 10.1523/jneurosci.0206-12.2012
|View full text |Cite
|
Sign up to set email alerts
|

Calcium-Permeable AMPA Receptors Provide a Common Mechanism for LTP in Glutamatergic Synapses of Distinct Hippocampal Interneuron Types

Abstract: Glutamatergic synapses on some hippocampal GABAergic interneurons exhibit activity-induced long-term potentiation (LTP). Interneuron types within the CA1 area expressing mutually exclusive molecular markers differ in LTP responses. Potentiation that depends on calcium-permeable (CP) AMPA receptors has been characterized in oriens-lacunosum moleculare (O-LM) interneurons, which express parvalbumin and somatostatin (SM). However, it is unknown how widely CP-AMPAR-dependent plasticity is expressed among different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
69
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(79 citation statements)
references
References 27 publications
(45 reference statements)
9
69
1
Order By: Relevance
“…In addition, our data indicate that in O/A interneurons ␣7 nAChRs can be synaptically activated by endogenous ACh released from cholinergic fibers. Like CP-AMPA receptors, ␣7 nAChRs are highly permeable to calcium (Bertrand et al, 1993;Séguéla et al, 1993;Fucile, 2004) and exhibit a strong inward rectification due to the voltage-dependent block of spermine (Haghighi and Cooper, 1998). Interestingly, nAChRs are several times more sensitive to spermine block than AMPA and kainate receptors (Haghighi and Cooper, 1998).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In addition, our data indicate that in O/A interneurons ␣7 nAChRs can be synaptically activated by endogenous ACh released from cholinergic fibers. Like CP-AMPA receptors, ␣7 nAChRs are highly permeable to calcium (Bertrand et al, 1993;Séguéla et al, 1993;Fucile, 2004) and exhibit a strong inward rectification due to the voltage-dependent block of spermine (Haghighi and Cooper, 1998). Interestingly, nAChRs are several times more sensitive to spermine block than AMPA and kainate receptors (Haghighi and Cooper, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…This may strongly influence feedback inhibitory circuits, network oscillations and information processing in the hippocampus. Whether nAChRs are instrumental in inducing LTP at glutamatergic synapses of other hippocampal interneuron types known to express calciumpermeable AMPA receptors (Szabo et al, 2012) remain to be established.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…8 D, F; n ϭ 5, p Ͻ 0.05, t test). To test whether the CPA application affects presynaptic Ca 2ϩ release (Simkus and Stricker, 2002;Martín and Buño, 2003), which could contribute to plastic changes, we analyzed the properties of sEPSCs and evoked EPSCs (eEPSC) as well as the area under curve of TBS-evoked somatic responses in control and in the presence of CPA. Our data showed that the amplitude, frequency, and kinetics of sEPSCs were not affected by CPA application (amplitude control: 18.8 Ϯ 0.4 pA; amplitude CPA: 17.7 Ϯ 0.3 pA; frequency control: 5.1 Ϯ 0.8 Hz; frequency CPA: 6.8 Ϯ 1.7 Hz; rise control: 0.36 Ϯ 0.01 ms; rise CPA: 0.35 Ϯ 0.03 ms; decay control: 2.33 Ϯ 0.09 ms; decay CPA: 2.25 Ϯ 0.06 ms; n ϭ 4, p Ͻ 0.05, MannWhitney test).…”
Section: Spatial Profile Of Dendritic Ca 2؉ Nonlinearitiesmentioning
confidence: 99%